PATH-03. HIGH-GRADE NEUROEPITHELIAL TUMOR SHOWING BCOR IMMUNOPOSITIVITY WITHOUT EXON 15 INTERNAL TANDEM DUPLICATIONS IN A FIVE-YEAR-OLD BOY: A CASE REPORT. (4th December 2020) - Wakita, Shogo; Matsutani, Tomoo; Watanabe, Yosuke; Hirono, Seiichiro; Higuchi, Yoshinori; Iwadate, Yasuo; Ikeda, Zyunichiro; Yokoo, Hideaki
Abstract: Recent DNA methylation profiling clarified several rare entities of pediatric CNS tumors from institutionally-diagnosed primitive neuroectodermal tumors (PNETs). One of which is CNS high-grade neuroepithelial tumor with BCOR alteration (CNS HGNET- BCOR ), and it carries in-frame internal tandem duplications (ITD) of the BCL6 corepressor (BCOR ) in exon 15. In the report, we describe a case of immunohistologically-diagnosed CNS HGNET- BCOR, which lacks exon 15 ITD of BCOR . A five-year-old boy visited a local hospital complaining uncontrolled vomiting for two months, and magnetic resonance imaging (MRI) showed a large well-circumscribed mass in his left cerebellum with ventricular dilatation. He referred to our hospital, and an additional MRI revealed diffuse and weak enhancement of gadolinium and low ADC values in mass. Immediately, he underwent total removal of the tumor and ventricular drainage, and his consciousness recovered soon after surgery. The tumor presented high BCOR expression by IHC, but target PCR did not identify exon 15 ITD of BCOR. As the previously-reported clinical and imaging features of CNS HGNET- BCOR resembled our case, we clinically diagnosed it as a similar phenotype of CNS HGNET- BCOR without exon 15 ITD. He received 60 Gy of extended-local irradiation with concomitant temozolomide and discharged without any neurological deficits. Since BCOR alterations, including ITD, gene fusions, and mutations, play an oncogenic role in several cancers, the present case might harbor another gene aberration of BCOR .